CHRONOSTRATIGRAPHIC FRAMEWORK OF THE EXTERNAL LIGURIAN UNITS (LATE CRETACEOUS; NORTHERN APENNINES; ITALY) BASED ON CALCAREOUS NANNOFOSSILS - Catanzariti, Rita; Perilli, Nicola (Ofioliti, 2011)
The study of calcareous nannofossil assemblages recovered from the External Ligurian Units allows us (1) to reconstruct the distribution patterns of selected Late Cretaceous taxa; (2) to identify the biohorizons helpful in recognizing and characterizing the standard zones of Sissingh (1977); some of which have been grouped; and (3) to propose a synthesis of the ages achieved until now for the External Ligurian Units. According to the available dataset; rooted on published and unpublished data; the here proposed biostratigraphic scheme is based on 24 age-indicative taxa and 16 first occurrences; and its biostratigraphic resolution is comparable with the resolution of the scheme of Sissingh (1977); only considering FOs. Calcareous nannofossils are hence a fossil group useful to furnish a new and more complete chronostratigraphic framework of the main External Ligurian Units; helpful to better constrain the tectono-sedimentary and the geodynamic evolution of the Western Tethys Domain.